The Economic Impact of Shale Gas Production in the U.S. - YANG, YANG. (2017)
Abstract: Energy is important to our daily lives. A price change of one energy type may influence our consumption choices, commodities prices and industry production. For the United States, shale gas is becoming a promising source of natural gas because of the rapid increase in its reserve and production capacity. Shale gas production is projected to be a large proportion of U.S. gas production, as predicted by Energy Information Administration (EIA). However, besides knowing the big picture, more details are needed before characterizing shale gas as a "game changer." It is interesting to address questions like to what extent the production of shale gas could affect other industries' production, stabilize commodities' prices, and what are the impacts on factor payments, capital returns, labor payments and household consumption. In this study, I use a CGE model to measure the impact on industry and the change in social welfare associated with shale gas production.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Economics.; Advisor: Drusilla Brown.; Committee: Jeffrey Zabel, and Yannis Ioannides.; Keywords: Economics, and Energy.